A Guinea Pig Model of Airway Smooth Muscle Hyperreactivity Induced by Chronic Allergic Lung Inflammation: Contribution of Epithelium and Oxidative Stress - Vasconcelos, Luiz Henrique César (Front Pharmacol, 2019)
Asthma is a heterogeneous disease of the airways characterized by chronic inflammation associated with bronchial and smooth muscle hyperresponsiveness. Currently, different murine models for the study of asthma show poor bronchial hyperresponsiveness due to a scarcity of smooth muscle and large airways, resulting in a failure to reproduce smooth muscle hyperreactivity. Thus, we aimed to standardize a guinea pig model of chronic allergic lung inflammation mimicking airway smooth muscle hyperreactivity observed in asthmatics (Asth). Animals were randomly divided into a control group (Ctrl), which received saline (0.9% NaCl), and the Asth group, subjected to in vivo sensitization with ovalbumin (OVA) nebulization. Morphological analysis was performed by hematoxylin-eosin staining. Bronchial hyperresponsiveness was evaluated by nebulization time in the fifth, sixth, and seventh inhalations (NT5-7) and tracheal isometric contractions were assessed by force transducer. Total antioxidant capacity was measured by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and protein expression by Western blot. Histologically, the Asth group developed peribronchial cellular infiltrate, epithelial hyperplasia and smooth muscle thickening. After the fourth nebulization, the Asth group developed bronchial hyperreactivity. The trachea from the Asth group contracted after in vitro stimulation with OVA, differing from the Ctrl group, which showed no response. Additionally, airway smooth muscle hyperreactivity to carbachol and histamine was observed in the Asth group only in intact epithelium preparations, but not to KCl, and this effect was associated with an augmented production of reactive oxygen species. Moreover, lung inflammation impaired the relaxant potency of isoproterenol only in intact epithelium preparations, without interfering with nifedipine, and it was found to be produced by transforming growth factor-β negative modulation of β adrenergic receptors and, furthermore, big-conductance Ca(2+)-sensitive K(+) channels. These effects were also associated with increased levels of phosphatidylinositol 3-kinases but not extracellular signal-regulated kinases 1/2 or phosphorylation, and augmented α-actin content as well, explaining the increased smooth muscle mass. Furthermore, pulmonary antioxidant capacity was impaired in the Asth group. Therefore, we developed a standardized and easy-to-use, reproducible guinea pig model of lung inflammation that mimics airway smooth muscle hypercontractility, facilitating the investigation of the mechanisms of bronchial hyperresponsiveness in asthma and new therapeutic alternatives.